O ensino do saxofone popular na graduação em música da UFPB: estratégias e processos didático-pedagógicos - Silva, Katyucha Góis da (2016)
The current work aims at understanding the didactic-pedagogical strategies and processes used in saxophone lessons (popular style) in the undergraduate degree at the Federal University of Paraíba. The specific goals of this research are: identifying how the teacher selects and organizes the saxophone technical-interpretative contents, identifying the didacticpedagogical strategies used in his classes, and relating such contents and didactic-pedagogical strategies to the students’ education process. In order to obtain answers to our questions, we carried out a bibliographical research, in which we used the significant learning theory by David Ausubel as the main theoretical pillar, supported by definitions of context and formal and informal teaching and learning practices. The tools employed for data collection were semi-structured interviews, participant observation, and documental research. At the end of the research, we perceived that the teacher designs the popular saxophone discipline upon two main axes – technical placement and the study of repertoire focused on improvisation – thus carrying out a deep technical and interpretative study which regards scales and intervals as basic contents. In this work, the teacher develops the technical enhancement of his pupils from an extensive study of methods and scales, however not merely reproducing such material, but employing strategies designed to meet each student’s reality, intending to motivate them to reflect and take part in their own education. In this discipline, the contents are organized in a graded manner in order to make the link between them stronger, besides the acquisition of improvising skills by the students, providing them with the necessary resources so that their students take part in meaningful learning. At the end of our work, we concluded that the didactic-pedagogical strategies, used by teacher Heleno Feitosa in his lessons, are permeated by formal and informal teaching practices, making popular saxophone learning at Federal University of Paraíba more contextualized, regarding the popular musician daily basis, providing his students with more consistent professional development.